Methods for the analysis of Sunset Yellow FCF (E110) in food and beverage products-a review - Kobun Rovina; Pillai Perumal Prabakaran; Shafiquzzaman Siddiquee; Sharifudin MD SHAARANI (Elsevier, 2016)
Food colorants are categorized into natural and synthetic dyes. One of the famous synthetic food dyes is Sunset Yellow FCF (E110) which belongs to the family of azo dyes and widely used in food industry. However, Sunset Yellow has positive and negative effects as well, by giving attractive physical appearance and consumer acceptance. At the same time, it can cause as attention deficit hyperactivity disorder (ADHD), is a group of behavioural symptoms that include inattentiveness, hyperactivity and impulsiveness, cancer and some other health effects with an excess consumption. Due to the arising of the health issues for mankind, researchers should give more priority to develop advance techniques for determination of Sunset Yellow in food and beverage products. The main aim of this review paper is critically discussed on the acceptable daily intake (ADI), toxicology, extraction methods, and analytical and electrochemical sensor methods for determination of Sunset Yellow.